Study on the correlation between anti-ribosomal P protein antibody and systemic lupus erythematosus. Issue 20 (15th May 2020) - Wang, Yanping; Luo, Peng; Guo, Ting; Zou, Lin; Shi, Jing; Chen, Pu
Abstract : Abstract: The aims of this study were to compare diagnostic value of anti-ribosomal P protein antibody (anti-P), anti-Smith antibody (anti-Sm), anti-double-stranded DNA antibody (anti-dsDNA), anti-nucleosome antibody (ANuA), and anti-histone antibody (AHA) for systemic lupus erythematosus (SLE) as well as explore the correlation between anti-P and SLE. A retrospective study was performed with 487 SLE patients, 235 non-SLE rheumatic diseases, and 124 healthy subjects from January 2015 to December 2018. Clinical manifestations, laboratory results and Systemic Lupus Erythematosus Disease Activity Index (SLEDAI)-2000 scores were analyzed between anti-P/+/ and anti-P/−/ patients. SPSS19.0 statistical software was used for data analysis. The sensitivities of anti-P, anti-Sm, anti-dsDNA, ANuA, and AHA in SLE were 31.6%, 20.7%, 45.0%, 27.9%, and 14.6%, and the specificities were 99.2%, 99.4%, 98.9%, 98.3%, and 96.7%, respectively. Only 27.9% of SLE had a single positive anti-P while the other 4 antibodies were all negative. There were significant differences in the age of onset, skin erythema, urinary protein, creatinine and serum IgG, IgM, C3, C4 between anti-P/+/ and anti-P/−/ patients ( P  <  .05 ). When anti-Sjogren syndrome A antibody, anti-P were positive and anti-dsDNA was negative, the incidence of skin erythema was the highest (35.1%). Compared with anti-P/−/ patients, anti-P/+/ patients had higher SLEDAI scores ( P  <  .001 ). Anti-P, anti-Sm, anti-dsDNA, ANuA, and AHA have high specificity but poor sensitivity in the diagnosis of SLE; combined detection can greatly improve the detection rate. Anti-P is more valuable in the diagnosis of SLE when other specific autoantibodies are negative. SLE patients with positive anti-P have an earlier onset age and are more prone to skin erythema, lupus nephritis as well as higher disease activity.